2014
DOI: 10.1103/physrevb.90.115424
|View full text |Cite
|
Sign up to set email alerts
|

Interference of stimulated electronic Raman scattering and linear absorption in coherent control

Abstract: We consider quantum interference effects in carrier and photocurrent excitation in graphene using coherent electromagnetic field components at frequencies ω and 2ω. The response of the material at the fundamental frequency ω is presented, and it is shown that one-photon absorption at ω interferes with stimulated electronic Raman scattering (combined 2ω absorption and ω emission) to result in a net contribution to the current injection. This interference occurs with a net energy absorption ofhω and exists in ad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…Two-color photocurrents have been observed [7], and the expressions for the nonlinear optical response that describes them have been worked out in detail [8] for frequencies where states near the K points are important, with scattering included phenomenologically.Unlike most semiconductors, where two-color injection currents have been studied forhω < E g < 2hω, in undoped graphene one-photon absorption is possible at both 2ω and ω, and so complexities in the injected currents arise [9]. Yet since the lattice structure has inversion symmetry there are no one-color effects.…”
Section: Introductionmentioning
confidence: 99%
“…Two-color photocurrents have been observed [7], and the expressions for the nonlinear optical response that describes them have been worked out in detail [8] for frequencies where states near the K points are important, with scattering included phenomenologically.Unlike most semiconductors, where two-color injection currents have been studied forhω < E g < 2hω, in undoped graphene one-photon absorption is possible at both 2ω and ω, and so complexities in the injected currents arise [9]. Yet since the lattice structure has inversion symmetry there are no one-color effects.…”
Section: Introductionmentioning
confidence: 99%
“…However, the dependence of the nonlinearity on chemical potential, temperature, and the excitation frequency have not been systematically measured. Of the theoretical studies reported, most are still at the level of single particle approximations within different approaches, which include perturbative treatments based on Fermi's golden rule [25,26], the quasiclassical Boltzmann kinetic approach [1,2,27,28], and quantum treatments based on semiconductor Bloch equations (SBE) or equivalent strategies [3,[29][30][31][32][33][34][35][36][37][38]. When optical transitions around the Dirac points dominate, analytic expressions for the third order conductivities can be obtained perturbatively by employing the linear dispersion approximation [3,[35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Graphene has high electron mobility [18,19] and long spin relaxation lifetime [20][21][22][23]. The generation and manipulation of spin current by electronic [24,25] * Corresponding author:luom28@mail.sysu.edu.cn and optical [26][27][28][29][30][31] methods have been proposed theoretically and studied experimentally [32][33][34]. Single-layer graphenes (SLGs) and bilayer graphenes (BLGs) with the substrate proximity effect [35][36][37] or adatom doping [38] exhibit large values of spin-orbital coupling (SOC) that make the spintronic effect observable at room temperature.…”
Section: Introductionmentioning
confidence: 99%